3D deep electrical structure and seismogenic environment in the western section of the Zhangjiakou-Bohai fault zone - Peng, Yuanqian; Sun, Xiangyu; Zhan, Yan; Zhao, Lingqiang; Luo, Quanxing; Liu, Xuehua; Ran, Zhijie; Wang, Lisen (Frontiers in Earth Science, 2022)
The Zhangjiakou-Bohai fault zone (ZBFZ) is an important NW-trending active tectonic zone in North China. The western section of ZBFZ is characterized by frequent moderate and strong earthquakes. This is a typical tectonic area for studying seismic and volcanic activities. The three-dimensional (3D) deep electrical structure of the region was revealed by using 3D electromagnetic inversion of 143 magnetotelluric stations. The results suggest that the deep electrical structure in the western part of the ZBFZ is laterally heterogeneous. To the north of the Shangyi-Chicheng Fault (F4), the upper crust has a high resistivity structure (R), corresponding to the exposed Hanuoba basalts and metamorphic rocks. To the south of F4, high and low resistivity zones alternate, which is attributed to the complex faults and basin-range structures. In the middle crust, the low-resistivity structures (C1 and C2) gradually appear in the northwest and southeast of the study area, showing the characteristics of a high-resistivity structure sandwiched between two low-resistivity structures. In the lower crust, the two low-resistivity structures (C1 and C2) gradually join each other and the whole region becomes characterized by low resistivity. The Shangyi-Chicheng Fault (F4), the northern margin fault of the Huai’an Basin (F7), and the northern margin fault of the Huaizhuo Basin (F11) are definite electrical difference zones, which are connected to a low-resistivity layer in the crust. The results indicate that the focal depth of the 1998 M6.2 Zhangbei earthquake was between 12 and 15 km and its seismogenic fault was the Dahezhen-Hailiutu Fault (F3), which is concealed beneath the Hanuoba basalt area. It is speculated that owing to the neotectonic activities, the magma originated in the asthenosphere mantle rose and erupted on the surface near Datong, forming the Datong volcanic group. Then the magma continued to migrate and overflow along with the fractures in the NE direction, forming the Hannuoba basalts in the Zhangbei area. The existence of mantle thermal material in this area led to the migration of accompanying fluids to the middle and upper crust, resulting in fault sliding and frequent occurrence of moderate and strong earthquakes in this region.